KONSEP PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN - Tan, Fathnun (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
The failure of development in Indonesia has been blamed on the government's inability to eradicate widespread poverty. This is because development models tend to come from above and pay little attention to community participation. This does not provide opportunities for the community, especially the poor, to participate in the planning and decision-making process concerning the selection, planning, implementation, evaluation and monitoring of development programmes, so that the poor are only used as objects of development. The centralised development planning model of the past can indeed accelerate economic growth, but it is unable to overcome the impact of development, namely the widespread poverty. The concept of the community empowerment movement focuses on the fact that humans or human groups can experience obstacles and tries to create conditions that provide the possibility for every human being to be able to fulfil the task of actualising their existence as widely as possible. In Indonesia, empowerment was originally a term widely used by Non-Governmental Organisations (NGOs) to refer to efforts to strengthen communities, both socio-economically and politically. In other words, community empowerment is about making people have a bargaining position so that they can become active actors in the development process and not just objects of development.